Integrated microthermoelectric coolers with rapid response time and high device reliability - Li, Guodong; Fernandez, Javier Garcia; Lara Ramos, David Alberto; Barati, Vida; Perez, Nicolas; Soldatov, Ivan; Reith, Heiko; Schierning, Gabi; Nielsch, Kornelius (Nature Electronics, 2018)
Microthermoelectric modules are of potential use in fields such as energy harvesting, thermal management, thermal imaging and high-spatial-resolution temperature sensing. In particular, microthermoelectric coolers (µ-TECs)—in which the application of an electric current cools the device—can be used to manage heat locally in microelectronic circuits. However, a cost-effective µ-TEC device that is compatible with the modern semiconductor fabrication industry has not yet been developed. Furthermore, the device performance of µ-TECs in terms of transient responses, cycling reliability and cooling stability has not been adequately assessed. Here we report the fabrication of µ-TECs that offer a rapid response time of 1 ms, reliability of up to 10 million cycles and a cooling stability of more than 1 month at constant electric current. The high cooling reliability and stability of our µ-TEC module can be attributed to a design of free-standing top contacts between the thermoelectric legs and metallic bridges, which reduces the thermomechanical stress in the devices.
CRIS-Team Scopus Importer:2022-04-14